English Teachers' Directive Speech Acts in The Classroom at Elementary Schools - Aisya Rayya; Inayatu Dzil 'Izzati Al-latif; Intan Sapna Febria; Teguh Sarosa (Universitas Nusantara PGRI Kediri, 2026)
This study aims at examining directive speech acts (DSAs) used by English teachers in elementary school classrooms. Teachers apply DSAs, such as questions, requests, and recommendations, to help students. Using observation, recording, and interviews, the study was carried out in a Grade V classroom. According to the findings, teachers primarily used requests (33.33%) and questions (53.33%) to monitor student engagement, manage activities, and assess understanding. Advice (6.67%) and prohibitions (6.67%) were less frequent yet crucial for support and discipline. Questions became the most prominent type of directive speech act in this study because they play a central role in guiding classroom interaction. Through questions, teachers can check students understanding, keep their attention, and encourage participation. Compared to other directive speech acts, questions are more flexible and easier to adapt to the students’ limited English proficiency. This makes question the dominant and most effective strategy observed in the classroom. These results demonstrate how crucial directive speech acts are when instructing young students in English. The study offers useful suggestions for teacher preparation and contributes to pragmatic research.